2021
DOI: 10.3844/ijrnsp.2021.11.20
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Stress and Well-Being in Undergraduate Nursing Students in China and the UK

Abstract: To test the differences of resilience, stress and well-being and explore the correlations between nursing students in China and United Kingdom. Globally nursing is considered a demanding profession and increasing attention has been placed on the psychological well-being and resilience of undergraduate nursing students. Limited international comparative research of the interaction between resilience, stress and wellbeing has been reported. A cross-sectional correlational design was adopted with a purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 41 publications
(90 reference statements)
3
26
2
Order By: Relevance
“…It is similar to many other studies where the majority of students experienced a low level of stress [33], a mild level of stress [38] and moderate stress [10], [15], [23], [27]. In contrast, higher mean stress scores have been reported in other studies conducted among nursing undergraduates in Australia [6], China [11], [17] and the UK. Stress-related symptoms such as disturbed sleep patterns, loss of appetite and feeling nausea and vomiting were among nursing undergraduates in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It is similar to many other studies where the majority of students experienced a low level of stress [33], a mild level of stress [38] and moderate stress [10], [15], [23], [27]. In contrast, higher mean stress scores have been reported in other studies conducted among nursing undergraduates in Australia [6], China [11], [17] and the UK. Stress-related symptoms such as disturbed sleep patterns, loss of appetite and feeling nausea and vomiting were among nursing undergraduates in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…This was inconsistent with another study where a significant negative correlation between perceived stress level and resilience was found [41]. In contrast, some studies found resilience score was associated with age and intention to leave [11].…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations